WAPL-mediated removal of cohesin protects against segregation errors and aneuploidy - Haarhuis, Judith H I; Elbatsh, Ahmed M O; van den Broek, Bram; Camps, Daniel; Erkan, Hasan; Jalink, Kees; Medema, René H; Rowland, Benjamin D (Current biology, 2013)
The classical X shape of mitotic human chromosomes is the consequence of two distinct waves of cohesin removal. First, during prophase and prometaphase, the bulk of cohesin is driven from chromosome arms by the cohesin antagonist WAPL. This arm-specific cohesin removal is referred to as the prophase pathway [1-4]. The subsequent cleavage of the remaining centromeric cohesin by Separase is known to be the trigger for anaphase onset [5-7]. Remarkably the biological purpose of the prophase pathway is unknown. We find that this pathway is essential for two key mitotic processes. First, it is important to focus Aurora B at centromeres to allow efficient correction of erroneous microtubule-kinetochore attachments. In addition, it is required to facilitate the timely decatenation of sister chromatids. As a consequence, WAPL-depleted cells undergo anaphase with segregation errors, including both lagging chromosomes and catenanes, resulting in micronuclei and DNA damage. Stable WAPL depletion arrests cells in a p53-dependent manner but causes p53-deficient cells to become highly aneuploid. Our data show that the WAPL-dependent prophase pathway is essential for proper chromosome segregation and is crucial to maintain genomic integrity.